Kepatuhan Pasien HIV Dan AIDS Terhadap Terapi Antiretroviral Di RSUP Dr. Kariadi Semarang - Aji, Herlambang Sasmita (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2010)
ABSTRACTBackground : HIV-AIDS if not treated can lead to low quality of life and life expectancy is short, it is necessary to support the effort, care and treatment and prevention of transmission HIV-AIDS disease. Adherence therapy is crucial in supporting the success of antiretroviral therapy treatment. Method: This research was conducted with the observational method with cross sectional approach. Data collection techniques by way of interviews using structured questionnaires. Samples taken as many as 70 HIV-AIDS patients received Antiretrovial therapy. Analysis of data by using univariate analysis, bivariate analysis with Chi Square test and multivariate analysis using logistic regression analysis. Results : This study showed an association between perception of the benefits of treatment with antiretroviral therapy adherence (p value = 0000), self-efficacy with treatment adherence (p value = 0000), experience side effects with compliance with antiretroviral therapy antiretroviral therapy (p = 0.005), knowledge about treatment with antiretroviral adherence (p = 0000), the availability of drugs with antiretroviral therapy adherence (p = 0018), supported by case managers with adherence antiretroviral therapy (p = 0030). The variables that are not associated with antiretroviral therapy adherence is the perception of severity, perception of barriers, ease of access to services, family support, peer support, support team physician HIV-AIDS. Independent variables, the most dominant influence on antiretroviral therapy adherence is the knowledge of antiretroviral therapy (exp (B) = 68,098), and than experience side effects (exp (B) = 12.248) and the availability of drugs (exp (B) = 10,260).Keywords: HIV, AIDS, patients, adherence, antiretroviral, therapy.